2009
DOI: 10.1242/dev.026666
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans CARMIL negatively regulates UNC-73/Trio function during neuronal development

Abstract: Whereas many molecules that promote cell and axonal growth cone migrations have been identified, few are known to inhibit these processes. In genetic screens designed to identify molecules that negatively regulate such migrations, we identified CRML-1, the C. elegans homolog of CARMIL. Although mammalian CARMIL acts to promote the migration of glioblastoma cells, we found that CRML-1 acts as a negative regulator of neuronal cell and axon growth cone migrations. Genetic evidence indicates that CRML-1 regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…In CARMIL1 knockdown cells, Rac1 activity was decreased, consistent with inhibition of lamellipodia. In addition, we found that CARMIL1 associates with the Rac-GEF Trio, as recently observed in C. elegans (Vanderzalm et al, 2009). Thus, CARMIL1 may control lamellipodial actin assembly via effects on Trio and Rac1.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In CARMIL1 knockdown cells, Rac1 activity was decreased, consistent with inhibition of lamellipodia. In addition, we found that CARMIL1 associates with the Rac-GEF Trio, as recently observed in C. elegans (Vanderzalm et al, 2009). Thus, CARMIL1 may control lamellipodial actin assembly via effects on Trio and Rac1.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, in CARMIL1i cells, the level of active Rac1 did not change. A recent study in C. elegans found biochemical and genetic interactions between CARMIL and Trio/UNC-73, a large protein with both Rac-and Rho-GEF domains (Vanderzalm et al, 2009). We looked for a biochemical interaction between CARMILs and Trio in our cells, by coimmunoprecipitation.…”
Section: Effects Of Carmil1 On Lamellipodial Actinmentioning
confidence: 96%
“…By contrast, recent work indicates that UNC-73/Trio can also be negatively regulated by the CRML-1/CARMIL (Capping, Arp2/3, Myosin I Linker) protein. This decreases the levels of SAX-3/Robo at the membrane (Vanderzalm et al, 2009) (Fig. 4D).…”
Section: Slit/robo and Netrin 1/dcc Inter-regulationmentioning
confidence: 91%
“…Initially puzzled by this, we soon discovered Gian Garriga's group had identified a novel, conserved protein that can form a complex with UNC-73, capping Arp2/3 myosin I linker, CRML-1/CARMIL. 25,26 In growth cones, crml-1 loss can suppress unc-73 mutants, placing CRML-1 and UNC-73 in both a physical and functional pathway. In the dorsal epidermis crml-1 loss resulted in excessive protrusions, particularly at non-medial edges, where protrusions are normally absent.…”
Section: 24mentioning
confidence: 99%